Shaping ability and buckling resistance of TruNatomy, WaveOne gold, and XP-Endo shaper single-file systems - Neveen Ali Shaheen; Nahla Gamal Eldin Elhelbawy (Wolters Kluwer Medknow Publications, 2022)
Objectives: The target of the current study was to evaluate and compare the shaping ability and buckling resistance of various single-file systems (TruNatomy [TRN], WaveOne gold [WOG], and XP-Endo Shaper [XPS]). Materials and Methods: Thirty recently extracted human first mandibular molars were chosen with severely curved mesiobuccal (MB) canals. Following access cavity preparation and determination of working length, teeth were randomly divided into three groups (n = 10) according to the instrumentation technique used, Group 1 (TRN), Group 2 (WOG), and Group 3 (XPS). Preinstrumentation and postinstrumentation, cone-beam computed tomography images were recorded at 3, 5, and 8 mm from the apex representing apical, middle, and coronal levels under the same circumstances, superimposed, and then canal transportation was determined using a particular equation. For buckling resistance calculation, files were loaded in the axial direction of the shaft and the maximum load was determined during the deflection of the file. One-way analysis of variance and Tukey test at 5% significance level were used to analyze data. Pearson's correlation between shaping ability and buckling resistance was performed. Results: XPS and TRN displayed significantly less canal transportation than WOG at the coronal and middle levels. While WOG recorded the highest value of buckling resistance, XPS recorded the least. Conclusions: XPS and TRN preserved the original curvature slightly better than WOG, while WOG reported the highest buckling resistance. There was a positive correlation between canal transportation and instrument resistance to buckle. Clinical Relevance: Preservation of the original shape of the canal after instrumentation is beneficial.